Computational study of new 1, 2, 3-triazole derivative of lithocholic acid: Structural aspects, non-linear optical properties and molecular docking studies as potential PTP 1B enzyme inhibitor. (February 2019) - Singh, Ashima; Singh, Harjinder; Khurana, J.M.
Graphical abstract: Highlights: A novel 1, 2, 3-triazole derivative of lithocholic acid is prepared. Geometrical properties are investigated using DFT study. FMO, charge analysis, TDOS. RDG, ESP have been investigated. Non-linear optical properties are studied. Molecular docking studies as potential PTP 1B enzyme inhibitor. Abstract: We have reported synthesis of a novel 1, 2, 3-triazole conjugate of lithocholic acid by 1, 3-dipolar cycloaddition reaction. The molecular properties such as geometry, conformations, bond lengths and dihedral angles were investigated theoretically. The bond order analysis was performed using Wiberg bond order (WBO), Fuzzy bond order (FBO) and Laplacian bond order (MBO) method. Electronic properties of molecule such as electrostatic surface potential analysis, frontier molecular orbital analysis, reduced density gradient, total density of states, and global chemical reactivity indices have been investigated. The nonlinear optical properties were also investigated. Total dipole moment, mean polarizability and hyperpolarizability were found to be much higher than standard urea molecule which suggests that it could act as potential NLO material. The molecular docking calculations are also performed to investigate its potential as PTP 1B enzyme inhibitor.